Postoperative Opioid Use, Complications, and Costs in Surgical Management of Lumbar Spondylolisthesis. Issue 15 (1st August 2018) - Vail, Daniel; Azad, Tej D.; O'Connell, Chloe; Han, Summer S.; Veeravagu, Anand; Ratliff, John K.
Abstract : Study Design: Retrospective analysis on a national longitudinal database (2007–2014). Objective: To determine the association between arthrodesis and complication rates, costs, surgical revision, and postoperative opioid prescription. Summary of Background Data: Arthrodesis in patients receiving laminectomy for lumbar spondylolisthesis remains controversial. However, population-level evidence to support the use of arthrodesis remains limited. Methods: We identified 73, 176 patient records and used coarsened exact matching to create comparable populations of patients who received laminectomy or laminectomy with arthrodesis. We use linear and logistic regression models to analyze the relationship between arthrodesis and postoperative complications, length of stay, costs, readmissions, surgical revisions, and postoperative opioid prescribing. Results: Patients who underwent arthrodesis spent 1 more day in the hospital on average ( P  < 0.01), and had higher costs of care at their index visit ($24, 126, P  < 0.01), which were partially offset by lower costs of care over the 2 years following their procedure ($14, 667 less in arthrodesis patients, P  = 0.01). Patients with arthrodesis were less likely to have a surgical revision (odds ratio = 0.66, P  < 0.01). Patients with arthrodesis used more opioids in the first 2 months following their procedure, but had comparable opioid use to patients undergoing laminectomy without arthrodesis in all other postoperative months over the next 2 years, and were not more or less likely to convert to chronic opioid use. Postoperative opioid prescription varied dramatically across states ( P  < 0.01); geographic variation in opioid use is substantially greater than differences in opioid use based on procedure performed. Conclusion: Arthrodesis is associated with reduced likelihood of surgical revision and increased use of opioids in the first 2 months following surgery, but not associated with greater or lesser opioid use beyond the initial 2 postoperative months. Geographic variation in opioid use is substantial even after accounting for patient characteristics and for whether patients underwent arthrodesis. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text